Zróznicowanie dzialan ofensywnych pilkarzy noznych w wybranych meczach Mistrzostw Europy w 2008 r. - Buraczewski, T.; Cicirko, L.; Gawlik, D. (Polish Journal of Sport and Tourism, 2013)
Football training should be organized in view of the requirements of contemporary sports and should be analyzed based on data obtained by observing the best teams in action. The goal of this study was to compare the frequency and effectiveness of selected tactical and technical actions performed by footballers from winning and losing teams in selected matches from the Euro 2008. Material and methods. The study involved close observation of performances by 166 players from 11 countries in 8 matches (Turkey-Czech Republic 3:2; Turkey-Switzerland 2:1; Italy- France 2:0; Holland-France 4:1; Sweden-Greece 2:0; Spain-Sweden 2:1; Germany-Portugal 3:2; Spain-Germany 1:0). The total amount of game observation time equaled 720 minutes. Analysis was conducted by repeatedly viewing DVDs of matches and coding the results on a detailed observational spreadsheet containing a detailed breakdown of offensive actions such as attempting goals, passing the ball or 1v1 attacking. Results and conclusions. Analysis showed that winning teams were more effective in seven out of eight indexes, i.e.: overall effectiveness in offense, effectiveness in attempting goals, overall effectiveness in passing, effectiveness in passing in easy situations, and effectiveness in 1v1 attacking. Losing teams were more effective solely in the index for passing in difficult situations.